Subgingival microbiota and genetic factors (A-2570G, A896G, and C1196T TLR4 polymorphisms) as periodontal disease determinants - Castro-Casarrubias, Raúl; Castro-Alarcón, Natividad; Reyes-Fernández, Salvador; Salazar-Hernández, Elena; Vázquez-Villamar, Mirna; Romero-Castro, Norma Samanta (Frontiers in Dental Medicine, 2025)
BackgroundSubgingival microbiota play an important role in maintaining oral health. Subgingival dysbiosis leads to the aggregation of highly pathogenic bacteria, and the host’s genetics modulates the innate immune response. The interaction between these two factors plays an important role in the aggravation of periodontitis. Therefore, evaluating the association between the TLR-4 polymorphisms and subgingival microbiota in patients with periodontitis is necessary.MethodsWe included 58 cases with periodontitis and 53 controls without periodontitis in this study. A896G, A-2570G, and C1196T polymorphisms of the TLR4 gene were determined by the polymerase chain reaction and restriction fragment length polymorphism technique. The DNA–DNA checkerboard hybridization technique was used for the identification and quantification of 18 bacterial species of subgingival plaque.ResultsCutibacterium acnes occurred in greater number and frequency than other bacterial species (χ¯ 1.32 E + 05) in individuals with periodontitis. Patients with C. acnes had a higher risk [odds ratio (OR)= 3.82 (95% confidence interval (CI): 1.37–10.3)] of developing periodontitis (p < 0.05), as did those with orange and red complex bacteria (Treponema denticola, Tannerella forsythia, Porphyromonas gingivalis, Prevotella nigrescens, Prevotella intermedia, Fusobacterium periodonticum, Fusobacterium nucleatum, Eubacterium nodatum, and Campylobacter rectus). The A/G genotype of SNP -2570 of the TLR4 gene was identified as a risk factor for the development of periodontitis [OR = 2.28 (95% CI: 1.04–5.00)]. Furthermore, there was an antagonistic biological effect of the presence of bacteria such as Capnocytophaga gingivalis [OR = 0.44 (95% CI: 0.20–1.96)] and C. rectus [OR = 0.39 (95% CI: 0.18-0.87)] (p < 0.05). The A/G genotype of SNP-2570 was correlated with greater clinical attachment loss and periodontal pocket depth.ConclusionsThe agonistic or antagonistic biological effect of each bacterial species depends on the genotype present in each individual and the destruction processes of dental support tissues.